NARCISSISTIC FUNCTIONING IN DRUG ADDICTS: A PSYCHOPATHOLOGICAL STUDY USING THE RORSCHACH TEST - Amel Ghezal, (International Journal of Innovative Technologies in Social Science, 2025)
The fragility of narcissistic functioning observed in individuals with drug addiction was highlighted in a compulsive and urgent manner through a projective psychopathological study. The results were analyzed using a psychoanalytic framework focused on chronic addiction cases of various types. This analysis was based on three Rorschach test protocols and an examination of the "mental status" Data were gathered through a qualitative projective psychoanalytic method, which revealed a profoundly disturbed psychological state. This condition was marked by severe difficulties in self-representing and an inability to integrate the body image, largely due to intense anxiety linked to feelings of disintegration and annihilation. Furthermore, identity instability emerged as a core disturbance, significantly impairing the individual's capacity to maintain a stable narcissistic foundation.